Use of the mineral trioxide aggregate (MTA) in teeth with apical incomplete formation - Mendoza Cama, Lissete Liliana (2018)
We report the clinical case of an 8-year-old girl who came to the clinic with intense pain in dental piece 4.6. Periapical radiography was taken. The diagnosis was symptomatic irreversible pulpitis in young permanent tooth with incomplete apical formation in null stage 8. It was decided to perform the apicoformation treatment, using the (MTA)  Mineral Trioxide Aggregate: as an apical stop. The radiographic controls were performed at 1, 3, 11, 35 months and Cone Bean tomography 43 months after the end of treatment. The patient presented absence of clinical symptoms and, radiographically, deposits of bone tissue were observed at the apical level